PERMEN MAKNYUS UNTUK MENINGKATKAN SEMANGAT BELAJAR DAN PRESTASI SISWA â SISWI SDN GEBANG II SIDOARJO - Pratiwi, Cindha Riri; Jamazy, Achmad Aflah; Firnandi, Chairunnisa Rizky Alfi; Wicaksana, Pandu Pratama Nur; Ilamul, Achmad (Program Kreativitas Mahasiswa - Pengabdian Kepada Masyarakat, 2013)
Apropriate education is right for every single children who lives in Indonesia. It also happen for 22th student of SDN Gebang II Sidoarjo. Even SDN Gebang II Sidoarjo are located between 2 big city at East Java, Surabaya and Sidoarjo, school where located at remote village that known with Pucuâan, has not get electricity yet from PLN. Not appropriate access road made transportation vehicle cannot going pass through when rain is fall. This condition make SDN Gebang II facilities lack of facillities and then at 2011, Badan Akreditasi National gave them âCâ score for its acreditation. Lack of facility also afeccted to level of study at student, mostly they will left the school time behind for helping their parents harvesting of fish for five thousand rupiahs. Education is no longer important and interesting for the student of SDN Gebang II Sidoarjo. So through Public Service Student Creativity 2012, program to increase the spirit of learning from the students of SDN Gebang II Sidoarjo through variation type of learning media such as wall magazine, extracurricular, and multifunctional reading garden was runned.. Fruit syrup Apple Mangrove, piggy banks, pencil case, cultural keep environmental clean, organic and inorganic garbage sorting, garbage processing, confidence, creativity, innovation, originality, responsible attitude, dare to dream, as well as the spirit of learning and work to be the outcome of this program. The Program involves many volunteers end up good friends from college students to the public is expected to have sustainability and can be applied in remote areas more in support of the program equalization of education in Indonesia.